Wide Incidence Angle-Insensitive Metamaterial Absorber for Both TE and TM Polarization using Eight-Circular-Sector - Toan Trung Nguyen (Nature Portfolio, 2017)
Abstract In this paper, a wide incidence angle-insensitive metamaterial absorber is proposed using eight-circular-sector (ECS). Under normal incidence, the proposed absorber shows high absorptivity at different polarizations due to its symmetric geometry. Under oblique incidence, zero-reflection conditions for transverse electric (TE) and transverse magnetic (TM) polarization are different. Nevertheless, the proposed absorber shows high absorptivity under oblique incidence of both TE and TM polarization due to ECS. The performance of the proposed absorber was demonstrated with full-wave simulation and measurements. The simulated absorptivity at the specular angles exceed 90% and the frequency variation is less than 0.7% at approximately 9.26 GHz up to a 70° incidence angle in both TM and TE polarization. We built the proposed absorber on a printed-circuit board with 20 × 20 unit cells, and we demonstrated its performance experimentally in free space. The measured absorptivity at 9.26 GHz for the specular angles is close to 98% for all polarization angles under normal incidence. As the incidence angle is varied from 0° to 70°, the measured absorptivity at 9.26 GHz for the specular angles remain above 92% in both TE and TM polarization.